2001
DOI: 10.1046/j.1365-2664.2001.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the capture rate of cage‐trapped red foxesVulpes vulpesand an evaluation of rabies control measures in Britain

Abstract: Summary1. Methods used to control canids may differ in their relative effectiveness and how they 'sample' age and sex classes. However, there is little information on such biases. We utilized data from a population of known size and structure to quantify differences in the seasonal capture rate of foxes Vulpes vulpes of different age, sex and social status. The effects of home-range utilization and trap experience were also investigated. 2. The capture rate of juvenile ( < 1 years) foxes was highest in spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 34 publications
3
49
0
1
Order By: Relevance
“…Foxes were captured by netting from den sites or in baited box traps placed in residential gardens (Baker et al 2001a). All individuals were sexed, weighed, aged from tooth wear (Harris 1978) and ear tagged (Rototags, Dalton Supplies Ltd, Nettlebed, Henley-on-Thames, Oxfordshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Foxes were captured by netting from den sites or in baited box traps placed in residential gardens (Baker et al 2001a). All individuals were sexed, weighed, aged from tooth wear (Harris 1978) and ear tagged (Rototags, Dalton Supplies Ltd, Nettlebed, Henley-on-Thames, Oxfordshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In rural areas the proportion of the population that take baits is likely to be around 70-80% (Masson et al, 1999), whereas only about 40% bait uptake is reported in urban areas of the UK (Trewhella et al, 1991;Baker et al, 2001). Therefore we simulated a range of vaccination rates to study the effects of bait uptake on rabies control.…”
Section: Fox Controlmentioning
confidence: 99%
“…Sites that provide super-abundant food may also attract foxes from neighbouring territories or further away (e.g. Tsukada 1997) and movements between neighbouring territories can occur yearround (Baker et al 2001). Despite all the relevant variables, information is lacking about seasonal variation in feeding site attendance by both resident and trespassing foxes of each sex.…”
Section: Introductionmentioning
confidence: 99%
“…For example, attendance may be highest during spring/summer when parents or other group members are food provisioning cubs (Soulsbury et al 2008). In contrast, infrequent attenders at feeding sites would be expected most often during autumn and winter, coincident with dispersal and reproductive movements (Baker et al 2001;Soulsbury et al 2011). Alternatively, feeding sites could be used year-round, representing a stable source of food.…”
Section: Introductionmentioning
confidence: 99%